Study of Aggression Level among Education Students and Other Professional Students of Kashmir University - Khan, Mohammad Ashraf (Media Ilmu Keolahragaan Indonesia, 2018)
The main purpose of the study is to the comparison of Aggression level among Education Students and other professional Students. The Present study is state as, in Aggression Level of Education Students and other professional students i.e. M.B.A. and M.C.A. students of Kashmir University. For this study, the reserch was selected both from non-grantable as well as grantable Education College students and various professional students of Kashmir University. The students age was ranging from 18 years onward. The total Number of Students were thirty, 10 students from each department (Education, M.B.A and M.C.A) were selected by simple random Sampling Method. The data was collected by Standard Questionire and analysis and interpretation was done on the basis of special statistical techniques Viz. Mean, Standard Devivation and â€˜tâ€™ Test. In the earlier time the researcher was hypothesized that there will be a significant difference in Aggression level of Education and professional students of Kashmir University. The Aggression is part and parcel of life. Every situation is associated every action is associated with Aggression. The aggression levels various from different Education and professional students which is one of the biggest threats to their performance. The aggression level of Education students is different than that of professional students. So the researcher takes keen interest in taking the study entitled as â€œStudy Of Aggression level between Education and Professional Students of Kashmir University.â€